ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN MEMILIH HUNIAN APARTEMEN PANDAN WANGI RESIDENCE KOTA SAMARINDA - Tommy Syam Saam, Tommy Syam Saam Tommy Syam Saam (EKONOMIA, 2015)
Tommy Syam Saam, 2014, Analysis of Factors Affecting Consumer Memelilih Residential Apartment Pandan Wangi In Samarinda, under the guidance of Mr. Jonathan and Mrs. Eka Robin Yudhyani. The purpose of this study was to determine the effect of the price, location and environment of the consumer decision Memelilih Residential Apartment Pandan Wangi In Samarinda. Basic theory used is Marketing Management by using multiple linear regression analysis with 45 samples. The results showed: Calculated F value of 8.114 is greater than the F table value of 3.23 and with a significance of 0.000 <α 0.05, this shows the price variable (X1), Location (X2) and the environment (X3) has a significant influence on consumer buying decisions apartment.Thus the hypothesis, accepted. t value price variable (X1) of 3.059> t table of significance of 1.96 and 0.004 <α 0.05, indicating the price variable (X1) has a significant influence on consumer buying decisions apartment so the research hypothesis is accepted.  Location variable t value (X2) is 2.636> t table of significance of 1.96 and 0.012 <α 0.05, indicating a variable location (X2) has a significant influence on consumer buying decisions apartment so the research hypothesis is accepted Environment variables t value (X3), amounting to 2,567> t table of significance of 1.96 and 0.014 <α 0.05, indicating Environment variable (X3) with significant influence on consumer buying decisions apartment so the research hypothesis is accepted.